Approaching subthreshold-swing limit for thin-film transistors by using a giant-dielectric-constant gate dielectric. Issue 46 (28th August 2019) - Chen, Zhuo; Lan, Linfeng; Peng, Junbiao
Abstract : Low-temperature giant-dielectric-constant thin films (In0.0025 Nb0.0025 Ti0.995 O2 ) fabricated with RF sputtering are employed as the dielectrics for IZO-TFTs. Abstract : Low-temperature giant-dielectric-constant thin films (In0.0025 Nb0.0025 Ti0.995 O2 ) fabricated with simple radio frequency (RF) sputtering on glass substrates are employed as the gate dielectrics for thin-film transistors (TFTs) for the first time. The 380 nm-thick In0.0025 Nb0.0025 Ti0.995 O2 film exhibited a quasi-static capacitance of as high as 36 156 nF cm −2 with a quasi-static permittivity of 15 525 (and 7607 nF cm −2 at 1 kHz). Indium zinc oxide (IZO) TFTs with In0.0025 Nb0.0025 Ti0.995 O2 gate dielectrics exhibited high output current at low operation voltage and little hysteresis in the transfer curves between forward and reverse sweeps. The subthreshold swing (SS) of the IZO TFTs is 0.068 V dec −1, very close to the lowest limit of the SS of the field-effect transistors (0.06 V dec −1 ). The results also proves that the lowest limit of the SS (0.06 V dec −1 ) cannot be broken no matter how high the gate dielectric capacitance is (except for negative capacitors). The TFTs demonstrate the potential for the applications in low-power circuits or flat-panel displays.